PSYCHOLOGICAL FACTORS AFFECTING THE EFFECTIVENESS OF FIREFIGHTERS’ PROFESSIONAL ACTIVITIES IN EXTREME CONDITIONS - Karpenko, Yurii (Global Prosperity, 2025)
Abstract. The relevance of the study is determined by the increasing intensity and complexity of emergency situations, accompanied by high levels of psycho-emotional stress, risk to life, and the need for rapid decision-making, which highlights the need for an in-depth analysis of the psychological factors affecting the effectiveness of firefighters’ professional activities. The purpose of the article was to scientifically substantiate the psychological factors of the effectiveness of firefighters’ professional activities in extreme conditions. The research methodology was based on systemic, personality-activity, and comprehensive approaches using theoretical analysis of scientific sources, psychodiagnostic methods, expert assessment, correlation analysis (Pearson and Spearman coefficients), and methods of mathematical statistics. The empirical sample consisted of 186 firefighters and rescuers of the State Emergency Service of Ukraine with varying professional experience. The study found that the effectiveness of firefighters’ professional activities is determined by the coordinated interaction of cognitive, motivational, emotional-volitional, regulatory, psychophysiological, and personal components of psychological readiness. It was found that risk readiness is not a determining factor in professional self-realization, but rather that motivational and regulatory characteristics of personality play a significant role. Data was obtained on the lowest level of formation of motivational and regulatory components of psychological readiness in firefighters, regardless of their length of service. The practical significance of the results lies in the possibility of using them to improve the system of professional and psychological training of firefighters, develop psychological support programs, preventing professional burnout, and increasing the effectiveness of fire and rescue units in emergency situations.